Psychoanalysis: The Reasons Of Body Changing In A Movie Turning Red - Rosalia Floriani (Journal on Education, 2023)
When confronted with a challenge, individuals frequently experience anxiety. Numerous literary works depict the worry of the characters through the author's and characters' psychology. This study examines the psychology of the characters in the Disney film Turning Red. Mei Lee, a youthful, vivacious, and self-assured girl, is the film's primary character. Novels, poems, and films have examples of such works of literature. Freud discusses three types of anxiety: realistic anxiety, moral anxiety, and neurotic anxiety. The study employs qualitative descriptive methodologies. This study aims to determine why the main character in the film Turning Red undergoes physical transformations using Freudian anxiety types. According to this study, the main character experienced three types of anxiety. Realistic anxiety is the most prevalent type of anxiety. Anxiety occurs due to the dread of others caused by her body's transformation. It will cause others to fear her and consider her weird.